2021
DOI: 10.1001/jamapediatrics.2021.3348
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Physical Restraint Use for Pediatric Patients in the Emergency Department

Abstract: 2. Davies P, Lillie J, Prayle A, et al. Association between treatments and short-term biochemical improvements and clinical outcomes in post-severe acute respiratory syndrome coronavirus-2 inflammatory syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…39,40 In addition, racial and ethnic disparities in both pediatric physical and pharmacologic restraint use have been shown. 41,42 Although the adverse effects of restraint use have been well described in the literature, and there is insufficient evidence to support restraint use as a safe or effective intervention, restraints may be necessary at times to prevent injury to patients and providers. [43][44][45] The use of restraints should be avoided whenever possible.…”
Section: Restraint Usementioning
confidence: 99%
“…39,40 In addition, racial and ethnic disparities in both pediatric physical and pharmacologic restraint use have been shown. 41,42 Although the adverse effects of restraint use have been well described in the literature, and there is insufficient evidence to support restraint use as a safe or effective intervention, restraints may be necessary at times to prevent injury to patients and providers. [43][44][45] The use of restraints should be avoided whenever possible.…”
Section: Restraint Usementioning
confidence: 99%
“…The intensity of acute patient care can in fact intensify race-based differences in care. Among other metrics, the use of seclusion, and of mechanical or chemical restraints is telling: their use is signi cantly higher among Black than white patients, both in adults (Nash et al, 2021;Smith et al, 2021) and in children and adolescents (Donovan, Plant, Peller, Siegel, & Martin, 2003; Martin, Krieg, Esposito, Stubbe, & Cardona, 2008). Our study showed that Black children were four times as likely to be restrained or secluded and Hispanics were 50% more likely to be restrained or secluded.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is that it does not thoroughly investigate the impacts of racism or poverty exposure on restraint use. A large cross‐sectional study in one New England health system demonstrated racial disparities in physical restraint use in children in the emergency department, which persisted after adjusting for sociodemographic and clinical characteristics 5 . Children with public insurance were also more likely to have physical restraints utilized, signaling socioeconomic disparities 5 .…”
mentioning
confidence: 99%
“…5 Children with public insurance were also more likely to have physical restraints utilized, signaling socioeconomic disparities. 5 Currently, it remains unclear whether similar racial and socioeconomic disparit- In the interim, we also need to explore medication effectiveness and safety for pharmacologic restraints in children. Medication classes varied across hospitals, reflecting limited existing evidence on medication effectiveness and safety to guide medication choice.…”
mentioning
confidence: 99%
See 1 more Smart Citation